Numerical modeling of a helical TE CO2 laser with a long output pulse - Sh. Al-Hawat; S. Al-Sheikh Salo (Results in Optics)
A previous computational program written in FORTRAN was modified to characterize a homemade helical transversely excited (TE) CO2 laser with a long output pulse.The power and intensity of the laser output pulse, the laser levels population and population inversion between two effective vibrational levels (0001) and (1000) of the laser, in addition to the temperatures of these levels and laser gain factor and the excitation rates and laser pulse energy were calculated for pressure varied between 45 and 85 mbar and voltage between 9 and 12 kV with a mixture ratio of CO2:N2:He = 1:1:3.A comparison between the measured and calculated energy and power of the laser output pulse was carried out, and gave a good agreement between them. Among the results, the maximum power reached 198 W, with pulse duration of 80 µs, and pulse energy of 15.48 mJ corresponding to pressure 85 mbar and voltage of 10 kV.